2015
DOI: 10.1089/cap.2015.0075
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis: Reduced Risk of Anxiety with Psychostimulant Treatment in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Meta-analysis suggests that treatment with psychostimulants significantly reduced the risk of anxiety when compared with placebo. This finding does not rule out the possibility that some children experience increased anxiety when treated with psychostimulants, but suggests that those risks are outweighed by the number of children who experience improvement in anxiety symptoms (possibly as a secondary effect of improved control of ADHD symptoms). Clinicians should consider rechallenging children with ADHD who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…For anti‐ADHD medications, we included three NMAs 49,144,145 , 11 MAs 146‐156 , 12 RCTs 157‐168 also included in those NMA/MAs, five additional RCTs 169‐173 , and five cohort studies 99,174‐177 . There were 148,664 youth on anti‐ADHD medications, including 28,834 across 298 RCTs after eliminating duplicated RCTs in multiple NMA/MAs (27,188 in NMA/MAs, 1,646 in additional RCTs), and 119,830 in five cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…For anti‐ADHD medications, we included three NMAs 49,144,145 , 11 MAs 146‐156 , 12 RCTs 157‐168 also included in those NMA/MAs, five additional RCTs 169‐173 , and five cohort studies 99,174‐177 . There were 148,664 youth on anti‐ADHD medications, including 28,834 across 298 RCTs after eliminating duplicated RCTs in multiple NMA/MAs (27,188 in NMA/MAs, 1,646 in additional RCTs), and 119,830 in five cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The comorbidity between OCD and anxiety symptoms has been demonstrated over the years, with some papers reporting that anxiety disorders are the most frequent comorbid conditions in OCD (Diniz et al, ), with frequencies that range from 62% (Torres et al, ) to 75.8% (Ruscio et al, ). Pediatric studies suggest ADHD is a common source of anxiety symptoms in children (Sciberras et al, ) and that successfully treating ADHD symptoms with psychostimulant medications significantly reduces anxiety (Coughlin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent Cochrane Systematic Review of nonrandomized studies found that rates of anxiety, sadness, and irritability with MPH treatment were 18.4%, 16.8%, and 17.2%, respectively (Storebo et al 2018), whereas a Cochrane Systematic Review of randomized controlled trials (RCTs) found no significant effect of MPH on the AEs of ''worried or anxious'' (risk ratio, (Storebo et al 2016). Additional recent meta-analyses and individual studies found that MPH reduced risk of both anxiety (Gurkan et al 2010;Golubchik et al 2014aGolubchik et al , 2014bCoughlin et al 2015;Snircova et al 2016;Pozzi et al 2018) and irritability (Efron et al 1997;Sonuga-Barke et al 2009;Stuckelman et al 2017;Pozzi et al 2018;Winters et al 2018). Our findings illustrate that both scenarios can in fact be at play-MPH may worsen or improve these emotional symptoms, with the key to predicting direction of effect hinging upon baseline anxiety/depression and oppositionality levels.…”
Section: Discussionmentioning
confidence: 99%